Mastering OpenCV 4 : A comprehensive guide to building computer vision and image processing applications with C++, 3rd Edition /: A comprehensive guide to building computer vision and image processing applications with C++, 3rd Edition. (2018) - Shilkrot, Roy; Millán Escrivá, David
No abstract available